Abcc10 status affects mammary tumour growth, metastasis, and docetaxel treatment response - Domanitskaya, N (Nature Publishing Group, 2014)
BACKGROUND: Resistance to chemotherapeutic agents is a major obstacle to cancer treatment. A group of ABC efflux pumps, the Multidrug Resistance Proteins, is a source of resistance. Herein, we investigated the role of ABCC10 in mammary tumours, given the important role we have defined for ABCC10 in transporting taxanes, and the recognition that some ABCC proteins have roles in tumour growth. METHODS: ABCC10 expression was correlated to human breast cancer subtype using breast tissue microarrays. Real-time quantitative PCR and western blot analysis were used to examine ABCC10 expression in human breast cancer lines. Abcc10(−/−) mice were crossed to MMTV-PyVmT mice to produce Abcc10(−/−) vs Abcc10(+/+) mammary tumours and derivative cell lines. We used allograft and cellular assays to perform baseline and drug sensitization analysis of tumours and cell lines. RESULTS: Clinical sample analyses indicated that ABCC10 was more highly expressed in Her2+ and ER+ than in Her2−, ER−, and triple-negative breast cancer. Unexpectedly, PyVmT; Abcc10(−/−) tumours grew more rapidly than PyVmT; Abcc10(+/+) tumours and were associated with significantly reduced apoptosis and metastasis. PyVmT; Abcc10(−/−) lines were less migratory than PyVmT; Abcc10(+/+) lines. Finally, we showed increased survival of docetaxel-treated MMTV-PyVmT; Abcc10(−/−) mice compared with wild-type mice. CONCLUSIONS: These data identify roles for Abcc10 in breast cancer pathogenesis and in vivo docetaxel resistance.